"Sugar" tumor lung. Rare clinical case - A. I. Shevchenko; Yu. O. Shatovskyi; A. P. Melnychuk; O. M. Andrianov (Zaporozhye State Medical University, 2018)
Aim. Determination of the degree of malignancy and prognosis of the disease in patients with a "sugar" lung tumor. Material and methods. The case of a light-cell ("sugar") lung tumor in a 76-year-old patient is described and analyzed. Results. The size and rate of growth of nodal formations in the lungs have a high correlation with the probability of their malignancy. The benign formations are either very small (less than 1 month in inflammatory processes), or very large (more than 16 months) time duplication of tumor mass. Lack of growth of a solid (dense) node within 2-3 years is a reliable criterion for its benign quality. The time to double the tumor mass of malignant tumors is usually in the range of 40 to 360 days. The time to double the tumor mass in this patient is 379 days. Conclusion. The light-cell or "sugar" tumor is more likely to be a highly differentiated malignant tumor with a fairly prolonged time doubling of tumor mass than benign tumor. The low level of proliferative activity of the tumor, coexpress of vimentinum also indicates this.